2017
DOI: 10.1016/j.physbeh.2016.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in aggression and cortisol levels in zebrafish subjected to unpredictable chronic stress

Abstract: Chronic stress may cause physical, behavioral and neuropsychiatric changes, affecting the health condition of an individual. Aggression is a universal behavior with great relevance on human and animal social systems. Despite studies showing the influence of chronic stress on aggression, the effects of unpredictable chronic stress (UCS) on aggressive behavior in male and female zebrafish remain unknown. Thus, the aim of this study was to evaluate the effects of UCS on the aggressive behavior and cortisol levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 42 publications
10
67
1
2
Order By: Relevance
“…We demonstrated for the first time that UCS protocol induced several changes in redox homeostasis in the zebrafish brain and revealed that EE has a protective effect against the oxidative stress induced by the UCS protocol. UCS protocol induces several biochemical changes in the zebrafish brain and through sustained activation of the neuroendocrine axis leads to increased cortisol levels (Piato et al, 2011;Manuel et al, 2014;Marcon et al, 2016;Rambo et al, 2017;Song et al, 2017). This was confirmed by the results recently published in our previous study, which showed that the UCS protocol increased cortisol levels while EE for 21 or 28 days prevented this increase (Marcon et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We demonstrated for the first time that UCS protocol induced several changes in redox homeostasis in the zebrafish brain and revealed that EE has a protective effect against the oxidative stress induced by the UCS protocol. UCS protocol induces several biochemical changes in the zebrafish brain and through sustained activation of the neuroendocrine axis leads to increased cortisol levels (Piato et al, 2011;Manuel et al, 2014;Marcon et al, 2016;Rambo et al, 2017;Song et al, 2017). This was confirmed by the results recently published in our previous study, which showed that the UCS protocol increased cortisol levels while EE for 21 or 28 days prevented this increase (Marcon et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…To induce stress in the zebrafish a UCS protocol was used which is already well established and described in our previous studies (Piato et al, 2011;Marcon et al, 2016;Rambo et al, 2017).…”
Section: Unpredictable Chronic Stress (Ucs) Protocolmentioning
confidence: 99%
“…Furthermore, it has been shown that differences in behavioural response may be sexually dimorphic. Recently, Rambo and colleagues showed that females under stress had increased locomotor activity in comparison to males, although males had increased cortisol levels (53). Here, we also observed different stress reactivity in both sexes; males showed increased bottom-dwelling response, covered longer distances and were more mobile than females when exposed to a novel environment.…”
Section: Discussionsupporting
confidence: 66%
“…Feeding behaviour is a complex process in fish (Volkoff & Peter, ). Additionally, stress produced as a result of infection may show gender differences in aggression, which under chronic stress conditions is higher in male than in female zebrafish (Rambo et al., ; Ramsay, Watral, Schreck, & Kent, ). Although behavioural studies were not conducted in this study, these results suggested the possibility that male zebrafish were more exposed to reiterate infections or less protected due to behavioural patterns that increased aggression and stress.…”
Section: Discussionmentioning
confidence: 99%